Treatment of POME using Fenton oxidation process: removal efficiency, optimization, and acidity condition - Saeed, M.O. (Taylor and Francis Inc., 2016)
In this study, the performance of a Fenton oxidation process was evaluated for the treatment of high-concentrated palm oil mill effluent (POME). Experiments were designed using the central composite design model of the response surface methodology (RSM). Four independent variables (reaction time, H2O2 concentration, Fe2+ ions concentration, and initial solution pH) and two dependent responses (COD and final solution pH) were investigated. The results show that at a low Fe2+ concentration and pH of about 3, an acceptable COD removal efficiency was achieved. At optimum conditions of pH 3.5 and 90 min reaction time, COD removal exceeded 85 and was successfully optimized by RSM. A significant model (pÂ <Â 0.0001) was obtained for final pH condition and statistically reached a satisfactory level with a correlation coefficient (R2) of about 0.71. This study, therefore, demonstrates the capacity of Fenton process to successfully remove COD from high-concentrated POME under the right combination of process variables. Â© 2016 Balaban Desalination Publications. All rights reserved.